KEEFEKTIFAN MODEL EXPERIENTIAL LEARNING DALAM PEMBELAJARAN MENULIS PUISI NARATIF SISWA KELAS VIII SMP NEGERI 2 DUA PITUE KABUPATEN SIDRAP [The Effectiveness of The Experiential Learning Model in Writing Learning The Narrative Point of The VIII Class Student of The 2 Dua Pitue Kabupaten Sidrap] - A. Irmawati (Kantor Bahasa Provinsi Maluku, 2019)
The Effectiveness of the Experiential Learning Model in Narrative Poetry Writing Learning in Second Pitue State Middle School 2 Sidrap Regency. This study aims to find out (1) the results of applying the model Experiential Learning in learning to write narrative poetry, (2) the results of application without using the model Experiential Learning in learning to write narrative poetry, (3) the effectiveness of the Experiential Learning model in writing narrative poetry of SMP Negeri 2 Dua Pitue, Sidrap Regency. The research design used is experimental. The population of this study was all eighth grade students of State Middle School 2 Dua Pitue Kabupaten Sidrap. The study sample consisted of two groups, namely grade students as a class experiment VIII.2 and VIII.3 class as a class kontrol. Sampling in this study using purposive sampling, meaning that the determination of the sample is done intentionally with the amount determined in accordance with the needs of the analysis. The technique used to determine this research data is a written test. Data analysis techniques use descriptive statistical techniques and inferential statistics. The results showed that (1) the application of the model had a significant effect seen from the pretest to posttest, namely the average value of the pretest was 64 to 80.74 after the posttest, ie an average value of 16.74, (2) the results of the application without using the model Experiential Learning shows the results of the average value pretest of 61.63 and becomes 71.59 after the posttest with an increase of 9.96, (3) the test of data analysis using Independent Sample T-tes shows the acquisition of p= 0,000 because p α α = 0.05 in degrees of freedom 44, then H which states the effectiveness of the application of models Experiential Learning in learning to write student narrative poetry is accepted. The results of this study conclude that the use of the Experiential Learning model is effective in learning to write narrative poetry in SMP Negeri 2 Dua Pitue, Sidrap Regency. Keefektifan Model Experiential Learning dalam Pembelajaran Menulis Puisi Naratif SMP Negeri 2 Dua Pitue Kabupaten Sidrap. Penelitian ini bertujuan mengetahui (1) hasil penerapan model Experiential Learning dalam pembelajaran menulis puisi naratif, (2) hasil penerapan tanpa menggunakan model Experiential Learning dalam pembelajaran menulis puisi naratif, (3) keefektifan model Experiential Learning dalam menulis puisi naratif siswa kelas VIII SMP Negeri 2 Dua Pitue Kabupaten Sidrap. Desain penelitian yang digunakan bersifat eksperimen. Populasi penelitian ini adalah keseluruhan siswa kelas VIII SMP Negeri 2 Dua Pitue Kabupaten Sidrap. Sampel penelitian terdiri dari dua kelompok, yaitu siswa kelas VIII.2 sebagai kelas eksperimen dan kelas VIII.3 sebagai kelas control. Penarikan sampel dalam penelitian ini menggunakan purposive sampling, artinya penentuan sampel dilakukan secara sengaja dengan jumlah yang ditentukan sesuai dengan kebutuhan analisis. Teknik yang digunakan untuk menentukan data penelitian ini adalah tes tertulis. Teknik analisis data menggunakan teknik statistika deskriptif dan statistika inferensial. Hasil penelitian menunjukkan bahwa (1) penerapan model Experiential Learning berpengaruh signifikan dilihat dari nilai tes awal ke tes akhir yakni nilai rata-rata tes awal sebesar 64 menjadi 80,74 setelah dilakukan tes akhir, yakni nilai rata-rata sebesar 16,74, (2) hasil penerapan tanpa menggunakan model Experiential Learning menunjukkan hasil nilai rata-rata tes awal sebesar 61,63 dan menjadi 71,59 setelah dilakukan tes akhir dengan peningkatan sebesar 9,96, (3) uji analisis data dengan menggunakan Independent Sample T-tes menunjukkan perolehan nilai p=0,000 karena p ≤ α =0,05 pada derajat kebebasan 44, maka H yang menyatakan keefektifan terhadap penerapan model Experiential Learning dalam pembelajaran menulis puisi naratif siswa diterima. Hasil penelitian ini menyimpulkan bahwa penggunaan model Experiential Learning efektif dalam pembelajaran menulis puisi naratif SMP Negeri 2 Dua Pitue Kabupaten Sidrap.